Much To Choose, Too Confused To Decide: Investigating Customer Confusion As A Mediator Of Information Overload And Decision Postponement - Cindy Desinta; Weni Novandari; Larisa Pradisti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of information overload on decision postponement, with customer confusion as a mediating variable, in the context of consumer behavior on e-commerce platforms in Indonesia. The study adopts a quantitative approach, conducted through a survey method using Google Forms as the data collection instrument, involving 150 active e-commerce users as respondents. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The findings reveal that information overload has a positive and significant effect on both customer confusion and decision postponement. Moreover, customer confusion is found to significantly mediate the relationship between information overload and decision postponement. These results support the Stressor–Strain–Outcome (SSO) theory and indicate that excessive information load can lead to confusion, which in turn causes consumers to delay decision-making. This study contributes to the enrichment of theoretical literature in the field of digital consumer behavior and provides practical implications for e-commerce practitioners in managing the information presented to consumers.